2007
DOI: 10.3758/bf03193306
|View full text |Cite
|
Sign up to set email alerts
|

Strength-based mirror effects in item and associative recognition: Evidence for within-list criterion changes

Abstract: Glanzer and Adams (1985, 1990) showed that the mirror effect is a prevalent feature of recognition memory performance. This effect describes the relationship between hit and false alarm rates across two conditions that differ in terms of their level of discrimination or overall accuracy. More specifically, the hit rate is higher and the false alarm rate is lower in the more accurate condition than in the less accurate condition. In other words, the false alarm rates mirror the order of the hit rates. Two gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
34
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 54 publications
5
34
0
1
Order By: Relevance
“…Hockley and Niewiadomski (2007) manipulated the strength of verbal associations by varying presentation time at study between lists and observed a strength-based mirror effect for associative recognition. Many researchers have attributed between-list strength-based mirror effects to changes in response bias (e.g., Hockley & Niewiadomski, 2007;Stretch & Wixted, 1998).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hockley and Niewiadomski (2007) manipulated the strength of verbal associations by varying presentation time at study between lists and observed a strength-based mirror effect for associative recognition. Many researchers have attributed between-list strength-based mirror effects to changes in response bias (e.g., Hockley & Niewiadomski, 2007;Stretch & Wixted, 1998).…”
Section: Resultsmentioning
confidence: 99%
“…Hockley and Niewiadomski (2007) manipulated the strength of verbal associations by varying presentation time at study between lists and observed a strength-based mirror effect for associative recognition. Many researchers have attributed between-list strength-based mirror effects to changes in response bias (e.g., Hockley & Niewiadomski, 2007;Stretch & Wixted, 1998). Hintzman, Caulton, and Curran (1994) argued that the presence or absence of a mirror effect depends not only on how a manipulation affects discrimination, but also on how the manipulation affects response bias.…”
Section: Resultsmentioning
confidence: 99%
“…Morrell et al (2002), in contrast, did not detect criterion shifts in the differential strengthening of words versus pictures. Also suggestive is Hockley and Niewiadomski's (2007) report that different criteria were applied to strong and weak single-word versus word-pair test probes. The test lists were mixed with regard to stimulus type (i.e., single or pair), although, in most of the experiments, not with regard to strength.…”
Section: Methodsmentioning
confidence: 99%
“…However, recently, other researchers have reported evidence suggesting that criterion shifts can occur within lists under some circumstances (e.g., Dobbins & Kroll, 2005;Han & Dobbins, 2008;Hockley & Niewiadomski, 2007;Rhodes & Jacoby, 2007;Singer & Wixted, 2006;Verde & Rotello, 2007). For example, Rhodes and Jacoby (2007) presented items at test in one of two locations on a screen, with the majority on one side of the screen being old items, and the majority on the other side being new.…”
mentioning
confidence: 99%